Brazilian migration to Guyana as livelihood strategy: a case study approach - CORBIN, Hisakhana Pahoona (2007)
This mixed method case study was conducted with focus on Brazilian migration to Guyana as a livelihood strategy. The study examined, described and analyzed the migration and adaptation process, and the socioeconomic and physical environmental impacts and concerns of the livelihood activities adopted by these migrants in Guyana. Questionnaires, interviews, documentaries, archival records, and observations (direct and participant) were utilized to gain an in-depth understanding of the phenomenon under study. The study confirms that throught a strong networking system, Brazilians from lower socioeconomic and cultural classes are able to adopt migration as a livelihood strategy, as they migrate in a step-wise manner along a well-defined route to Guyana. Maintaining this networking system, migrants have been able to respond swiftly to new livelihood activities both internally and internationally. In Guyana, mining and prostitution are the major livelihood activities that have given rise to both positive and negative socioeconomic consequences and concerns and, negative environmental impacts.